The Steel Yard And Neighborhood in 1540 (From Van Wyngard's Plan, Taken for Philip II. Of Spain) (Tufts Archival Research Center, 2005)
This illustration is from Walter Thornbury "Old and new London, a narrative of its history, its people, and its places, vol. 2"